TRUE RESISTANCE AND PSEUDORESISTANCE TO ASPIRIN - A. I. Martynov; E. V. Akatova; I. V. Urlayeva; O. P. Nicolin (Столичная издательская компания, 2015)
Low dose aspirin reduces the secondary incidence of myocardial infarction and stroke. Drug resistance to aspirin might result in treatment failure. Despite this concern, no clear definition of aspirin resistance has emerged, and estimates of its incidence have varied remarkably. Researchers from university of Pennsylvania (Philadelphia, the USA), led by Dr. Tilo Grosser, aimed to determine the specific phenotype of true pharmacological resistance to aspirin - such as might be explained by genetic causes. However the study failed to identify a single case of true drug resistance. Pseudoresistance, reflecting delayed and reduced drug absorption, complicates enteric coated but not immediate release aspirin administration.